Herman Melville's Moby-Dick - Archer, Mandy; Tempest, Annabel; Melville, Herman, 1819-1891 (Layton, Utah : Gibbs Smith, 2017)
Call me Ishmael. Some years ago I thought I would sail about a little and see the watery part of the world." Ishmael and his shipmates search the ocean far and wide. Will they ever find the white whale that sailors call, "Moby Dick"?
On board pages.
Age 3-5.
Keywords: Whales -- Juvenile fiction